Euthanasia and the nursing profession - Fasanella, G.; Corda, E. (Medicina e Morale, 1990)
The call for euthanasia is not new in history. Indeed, already in antiquity we find several advocates, such as the Greek philosopher Plato, and, in more recent times, one of the founding fathers of the inductive-experimental method of modern scientific research, Francis Bacon.....